Statistical Difficulties in Determining the Role of Race in Capital Cases: A Re-analysis of Data from the State of Maryland* - Berk, Richard (Journal of quantitative criminology, 2005)
In this paper, we re-analyze data used to study the role of race in capital cases in the state of Maryland. We show that when alternative, and arguably more appropriate, statistical procedures are applied, the racial effects reported in early work turn out to be very fragile. The methodological point is more general: conventional causal modeling with observational data is not likely to produce robust results for a variety of criminal justice applications.